A Pentaplex PCR Assay for the Detection and Differentiation of Shigella Species - Ojha, Suvash Chandra; Chan, Yean Yean; Ismail, Asma; Banga Singh, Kirnpal Kaur (Hindawi Publishing Corporation, 2013)
The magnitude of shigellosis in developing countries is largely unknown because an affordable detection method is not available. Current laboratory diagnosis of Shigella spp. is laborious and time consuming and has low sensitivity. Hence, in the present study, a molecular-based diagnostic assay which amplifies simultaneously four specific genes to identify invC for Shigella genus, rfc for S. flexneri, wbgZ for S. sonnei, andrfpB for S. dysenteriae, aswell as one internal control (ompA) gene, was developed in a single reaction to detect and differentiate Shigella spp. Validation with 120 Shigella strains and 37 non-Shigella strains yielded 100% specificity. The sensitivity of the PCR was 100 pg of genomic DNA, 5.4 × 104 CFU/ml, or approximately 120 CFU per reaction mixture of bacteria. The sensitivity of the pentaplex PCR assay was further improved following preincubation of the stool samples in Gram-negative broth. A preliminary study with 30 diarrhoeal specimens resulted in no cross-reaction with other non-Shigella strains tested. We conclude that the developed pentaplex PCR assay is robust and can provide information about the four target genes that are essential for the identification of the Shigella genus and the three Shigella species responsible for the majority of shigellosis cases.